A Rare Case and Literature Review of Endoscopic Endonasal - Tamil Selvi, Rajoo; Kevin Ng, Boon Han; Baharudin, Abdullah (Springer Nature, 2023)
We report a rare case of localized anterior clinoid mucocele (ACM) with acute visual loss and a literature review of the endoscopic endonasal surgery. We advocate that endoscopic endonasal approach is the best choice. To our knowledge there a limited report on localized ACM that treated via endoscopic endonasal approach